Von Fakiren, Bajaderen und Maharadschas. Der koloniale Blick in der frühen Porträtfotografie Indiens - Maria Buck (Historia.scribere)
This seminar paper analyzes 19th century portrait photographs in British-India, which were mainly made by and addressed at British citizens. Regarding the wide range of genres, it can be shown that these photographs hardly give a realistic image of India, but instead reflect the contemporaneous British view on the colony and its native inhabitants. Photography was therefore an essential instrument of colonial policy. By creating a culturally inferior “other”, it helped legitimating the British rule over India.